2020
DOI: 10.1109/access.2020.3025589
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Prediction of Available Parking Space Based on Machine Learning Approaches

Abstract: Reliable short-term prediction of available parking space (APS) is the basic theory of parking guidance information system (PGIS). Based on the Intelligent parking system at the Eastern New Town, Yinzhou District, Ningbo, China, this study collected the data of parking availability in the on-street parking areas. The variation characteristics of APS were investigated and analyzed at different spatialtemporal levels. Then the APS prediction models based on Gradient Boosting Decision Tree (GBDT) and Wavelet Neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…As previous research mentioned, 23,54 parking availability information is not only closely related with historical pattern, the attributes information and the variance of prediction time slots (i.e., 5 min ahead and 2 h ahead) also shows significant impact to the utility level. So, another key issues worth to review is hybridizing attention and LSTM networks for sequential data‐related research.…”
Section: Literature Review On Parking Prediction Methodologymentioning
confidence: 90%
See 1 more Smart Citation
“…As previous research mentioned, 23,54 parking availability information is not only closely related with historical pattern, the attributes information and the variance of prediction time slots (i.e., 5 min ahead and 2 h ahead) also shows significant impact to the utility level. So, another key issues worth to review is hybridizing attention and LSTM networks for sequential data‐related research.…”
Section: Literature Review On Parking Prediction Methodologymentioning
confidence: 90%
“…Combining the characteristics and skills of the neural network with the features and challenges of the parking perdition problem, several customized neural networks are designed to complete the forecasting task. Generally, current research mainly uses existing machine learning models, such as, Convolution Neural Network (CNN), 53,57 Recurrent Neural Network (RNN), 23,54,58,59 and then adopts them to address the real parking challenges. These models always include several features extraction parts: spatial features extraction, temporal features extraction, and attribute information.…”
Section: Literature Review On Parking Prediction Methodologymentioning
confidence: 99%
“…This section reviews three types of parking solutions: fixed sensing [8]- [10], mobile sensing [11]- [15], and data-based modeling [16], [17], whose features are summarized in Table I.…”
Section: Related Workmentioning
confidence: 99%
“…Ye et al [17] proposed a machine learning-based approach to make a short-term estimation of available parking spaces (APS). The prediction model is based on Wavelet Neural Network.…”
Section: Related Workmentioning
confidence: 99%
“…D. Chuan's study [11] showed that the XGB model outperformed the Random Forest model (RF) in terms of prediction performance and efficiency. X. Ye [12] proposed an algorithm for VPS prediction based on GBDT and Wavelet Neural Network (WNN). On this basis, an improved WNN algorithm combining Wavelet Analysis (WA) decomposition and Particle Swarm Optimization (PSO) was proposed.…”
Section: Introductionmentioning
confidence: 99%